2020
DOI: 10.3390/app10103647
|View full text |Cite
|
Sign up to set email alerts
|

Operational USLE-Based Modelling of Soil Erosion in Czech Republic, Austria, and Bavaria—Differences in Model Adaptation, Parametrization, and Data Availability

Abstract: In the European Union, soil erosion is identified as one of the main environmental threats, addressed with a variety of rules and regulations for soil and water conservation. The by far most often officially used tool to determine soil erosion is the Universal Soil Loss Equation (USLE) and its regional adaptions. The aim of this study is to use three different regional USLE-based approaches in three different test catchments in the Czech Republic, Germany, and Austria to determine differences in model results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
1
4
0
2
Order By: Relevance
“…This finding is in line with other authors criticising the approach of Panagos et al (2015), e.g. Boardman (2016a, 2016b), Auerswald (2016), andFiener et al (2020).…”
Section: Resultssupporting
confidence: 92%
“…This finding is in line with other authors criticising the approach of Panagos et al (2015), e.g. Boardman (2016a, 2016b), Auerswald (2016), andFiener et al (2020).…”
Section: Resultssupporting
confidence: 92%
“…A K factor map was provided by the LfL (derived from the soil properties given by the soil overview map of Bavaria at a scale of 1:25,000) based on the calculation in Schwertmann et al (1987. The LS2D factor was derived from the 5 m x 5 m DEM, following the approach of Desmet and Govers (1996. Assuming some soil conservation methods to be in place, e.g. partial contour ploughing, the P factor was set to 0.85 (Fiener et al, 2020). The tillage transport coefficient ktil depends on the tillage implement, tillage speed, tillage depths, bulk density, texture and soil moisture at time of tillage (Van Oost et al, 2006).…”
Section: Data 231 Soil Erosion Model Inputs and Parametersmentioning
confidence: 99%
“…There are no guidelines for appropriate application of models such as USLE; each user applies a different model variation based on the available data. Fiener et al (2020) compared three different USLE applications and observed substantial differences in the modelled soil loss, with up to 75% difference in the results. Thus, there are also problems and limitations with harmonization and standardization procedures in the application of USLE.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%